Allelopathy and Allelochemicals in Chamaecyparis obtusa Leaves for the Development of Sustainable Agriculture - Hisashi Kato-Noguchi; Kumpei Mori; Arihiro Iwasaki; Kiyotake Suenaga (Agronomy, 2024)
Chamaecyparis obtusa (Siebold et Zucc.) Endl. is cultivated in the temperate region of East Asia for its high-quality and profitable timber. The timber-processing industry produces a large amount of waste, such as tree bark, branches, and leaves, and finding ways to minimize such waste is economically and environmentally efficient. In the present study, the allelopathic activity and allelochemicals of the C. obtusa leaves were investigated to develop potential application methods. C. obtusa leaves were phytotoxic and associated leaf extracts significantly suppressed the growth of the weeds; Echinochloa crus-galli, Phleum pratense and Lolium multiflorum under laboratory conditions. The leaf powder applied onto the soil surface also suppressed the germination of E. crus-galli and P. pratense under greenhouse conditions. Hinokiic acid and (+)-dihydrosesamin were isolated from the leaves and structurally identified. Both compounds suppressed the growth of cress and P. pratense in a concentration dependent manner. When the leaves of C. obtua were applied as a soil additive, hinokiic acid and (+)-dihydrosesamin in the leaves potentially cause the growth inhibitory activity by leaching into the soil. These experiments showed that the leaves and the leaf extracts of C. obtusa are phytotoxic. These experiments also demonstrated that the leaves and the leaf extracts of C. obtusa have growth inhibitory potential against several plant species, and the leaves produce allelochemicals. Therefore, the leaves and leaf extracts of C. obtusa may be useful for weed suppression purposes. The leaf biomass of C. obtusa is frequently large and the timber processing industry produces significant leaf waste. The development of weed control products using waste leaves may be a solution to minimize the timber processing waste to reduce environmental impact and provide economic value. However, leaf material should be evaluated for weed suppression and herbicidal activity as a soil additive and also possible as a foliar spray under field conditions.